Impact of combined effect of penetrating and non-penetrating medium components on post-hypertonic lysis development in human erythrocytes - Chabanenko, Olena; Orlova, Natalia; Shpakova, Natalia (Problems of Cryobiology and Cryomedicine, 2020)
Abstract: In this research, a post-hypertonic lysis of human erythrocytes has been studied by varying the medium composition at dehydration stage. The osmolality of combined media, containing different concentrations of glycerol and NaCl was ~ 2370 mOsm/L. The level of post-hypertonic lysis of erythrocytes was shown as determined not by the total osmolality of dehydration medium, but glycerol concentration within the combined media. It was found that the nature of post-hypertonic lysis development of erythrocytes if using glycerol within the combined media at dehydration stage did not depend on preliminary cell saturation with cryoprotectant. A comparative study of post-hypertonic shock of erythrocytes at 37 and 0Â°C showed that in the latter case the cell hemolysis developed if using glycerol in lower concentration (10%) within the combined media (at 0°C the level of erythrocyte post-hypertonic lysis was 2.7 times higher). The observed effect may be due to a significant difference in the rates of transport for water and cryoprotectant through erythrocyte membrane at low temperatures. Probl Cryobiol Cryomed 2020; 30(3): 236–246